Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/molecules26020441
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 99mTc(I) Tricarbonyl Complexes Dual-Targeted at Tumoral Mitochondria

Abstract: For effective Auger therapy of cancer, the Auger-electron emitters must be delivered to the tumor cells in close proximity to a radiosensitive cellular target. Nuclear DNA is considered the most relevant target of Auger electrons to have augmented radiotoxic effects and significant cell death. However, there is a growing body of evidence that other targets, such as the mitochondria, could be relevant subcellular targets in Auger therapy. Thus, we developed dual-targeted 99mTc(I) tricarbonyl complexes containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 47 publications
4
32
2
Order By: Relevance
“…Most relevantly, the presence of a triglycine (Gly-Gly-Gly) linker between the BBN [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] sequence and the pyrazolyl-diamine chelator had a determinant influence on the nuclear internalization of the (radio)conjugates 129 and 131 , which was almost negligible when a Ser-Gly-Ser linker was used instead of Gly-Gly-Gly. Most probably, Gly-Gly-Gly acts as a cathepsin B cleavable linker that leads to the release of an AO-containing Re(I)/ 99m Tc(I) fragment inside the cells with better ability to reach the cell nucleus, as corroborated recently by in vitro enzymatic assays performed by the same authors with Re(I) tricarbonyl complexes [ 184 ]. The success of this dual-targeting strategy encourages the application of similar approaches to deliver classical DNA intercalators or G4-binders to the nucleus of tumor cells, aiming to achieve more selective and efficient anticancer therapies.…”
Section: Dna-targeted Radiocomplexesmentioning
confidence: 78%
“…Most relevantly, the presence of a triglycine (Gly-Gly-Gly) linker between the BBN [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] sequence and the pyrazolyl-diamine chelator had a determinant influence on the nuclear internalization of the (radio)conjugates 129 and 131 , which was almost negligible when a Ser-Gly-Ser linker was used instead of Gly-Gly-Gly. Most probably, Gly-Gly-Gly acts as a cathepsin B cleavable linker that leads to the release of an AO-containing Re(I)/ 99m Tc(I) fragment inside the cells with better ability to reach the cell nucleus, as corroborated recently by in vitro enzymatic assays performed by the same authors with Re(I) tricarbonyl complexes [ 184 ]. The success of this dual-targeting strategy encourages the application of similar approaches to deliver classical DNA intercalators or G4-binders to the nucleus of tumor cells, aiming to achieve more selective and efficient anticancer therapies.…”
Section: Dna-targeted Radiocomplexesmentioning
confidence: 78%
“…Thus, we considered the same propylenic linker to attach the AO to the dual-targeted chelator AO-Pz-BBN used to obtain the M-AO-BBN (M = Re and 99m Tc) complexes evaluated in this work (Figure 1). As for the BBN peptide, it contains the G3-BBN [7][8][9][10][11][12][13][14] sequence with a triglycine (G3) linker cleavable by cathepsin B, as we recently demonstrated for the Re-BBN complex [27]. The presence of the G3 linker is crucial to obtain an augmented accumulation of 99m Tc or AO chromophore in the nucleus of PC3 cells for dual-targeted M(I) (M = Re and 99m Tc) tricarbonyl complexes similar to M-AO-BBN.…”
Section: Chemistry and Radiochemistrymentioning
confidence: 99%
“…The obtained ESI(+) mass spectra confirmed the formation of the desired conjugates being observed the expected molecular ion peaks with isotope distributions in agreement with the proposed formulations. The complex 99m Tc-AO-BBN was synthesized by the reaction of the fac-[ 99m Tc(CO)3(H2O)3] + precursor with the dual-targeted chelator AO-Pz-BBN in an aqueous medium (Scheme 2), as we described previously for 99m Tc-BBN and 99m Tc-TPP-BBN [27]. All these 99m Tc complexes were purified by HPLC prior to their evaluation in the several biological studies reported in this work to separate the respective cold chelators.…”
Section: Chemistry and Radiochemistrymentioning
confidence: 99%
See 2 more Smart Citations